Essentials economics - Bishop, Matthew (London, 2006)
Economics is the ?study of how society uses its scarce resources? or, more snappily, ?the science of choices? that helps people make decisions about how to use such scarce things as land, labour, raw materials, capital, entrepreneurial spirit and time. An understanding of economics can therefore help people in politics and public service, in business and the professions, and even in their private life make decisions that will produce the results they are seeking to achieve. This book is a clear and lively guide to the essentials of economics, with entries that stretch from A to Z.
Keywords: Economics